Assessing the safety and efficacy of dinoprostone vaginal insert in pregnancy - Manickavasagam, M. Madhubala; Manickavasagam, M.; Ramalakshmi, M.; .Jeyajanani, R.; Reddy, V. Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Induction of labor (IOL) is a procedure used to achieve vaginal birth when the hazards of extending the pregnancy for either the mother or the infant outweigh the dangers of delivery. It is often used in high-risk pregnancies, although it can also be useful in low-risk groups, as demonstrated by A Randomized Trial of Induction Versus Expectant Management (ARRIVE) study. Methods: The cross-sectional study was conducted among 414 patients at Department of Obstetrics and Gynaecology tertiary care hospital. The study was conducted for one-year duration in pregnant women with maternal age >18 years, gestational week >37 weeks, and Bishop score <7 was included in the study with no signs of labor. Demographic details such as age, pregnancy history, and mode of delivery were recorded for comparison. Patients with no induction of labor were administered misoprostol and/or dinoprostone based on clinical conditions with further evaluation of maternal complications, delivery time, birthweight of the fetus, and fetal heart rate. Data were analyzed based on percentages and a chi-square test was used (p-value <0.05). Results: The mode of delivery did not significantly affect delivery outcomes (p=0.354), with assisted delivery being the most common (35.41%). Indication for induction was found to be significant (p=0.034), with non-progress of labor being the most common indication (55.2%). Maternal complications were not significantly associated with delivery outcomes (p=0.390), with 60 (14.49%) patients experiencing complications. The use of misoprostol reported a significant difference between modes of delivery with 74.93% of vaginal delivery, 19.47% with lower segment cesarean section (LSCS), and 5.60% with assisted delivery (p value <0.03). Conclusions: In low-risk pregnant women, the dinoprostone or misoprostol vaginal inserts are both safe and effective for inducing labor. Nulliparous individuals and those who did not get epidural analgesia during labor had a higher chance of caesarean section.